Influence of electron-phonon interaction on wannier–stark effect in macroporous silicon structures with SiO2 nanocoatings - L. A. Karachevtseva; Yu. V. Goltviansky; O. Yu. Sapelnikova; O. O. Lytvynenko; O. I. Stronska (Хімія, фізика та технологія поверхні, 2014)
We investigated the contribution of electron-phonon interaction to the broadening parameter of the Wannier–Stark ladders in oxidized macroporous silicon structures with different concentration of Si–O–Si states (TO and LO phonons). The obtained value of this parameter is much less than the Wannier–Stark ladder energy evaluated from giant oscillations of resonance electron scattering on the surface states of investigated structures. We determined the influence of broadening on the oscillation amplitude in IR absorption spectra as interaction of the surface multi-phonon polaritons with electrons and transformation of the resonance electron scattering in samples with low concentration of Si–O–Si states into ordinary scattering on ionized impurities for samples with high concentration of Si–O–Si states. The transformation takes place at the electron scattering lifetime coinciding with the period of electron oscillations in the presurface electric field.